Detection and Antibiotic Resistance of Salmonella spp. in Peranakan Etawa Goats - Rosyidi, Anwar; Ali, Muhammad; Sriasih, Made; Depamede, Sulaiman N.; Wariata, Wayan; Yusuf, Muhammad Deni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Diseases in goats reduce productivity and may cause reproductive disorders and zoonotic risks. Salmonellosis, caused by Salmonella spp., is an important livestock disease that can infect ruminants and poultry and contaminate animal products, affecting animal and human health. The purpose of this study was to determine the presence and the prevalence of Salmonella in Peranakan Etawa (PE) goats and to evaluate the antibiotic resistance profile of the isolates. Fecal samples were collected from 20 Peranakan Etawa goats and examined for the presence of Salmonella. Data on Salmonella cases and inhibition zone diameters (mm) obtained from antibiotic susceptibility testing were analyzed descriptively. The goats were managed under a semi-intensive system. They were fed odot grass supplemented with concentrate and silage additives, provided with well water as a drinking source, with feed troughs cleaned once daily and manure removed weekly. No anthelmintic treatment had been administered during the previous eight months. The results indicated that Salmonella infection was detected in 5% of the PE goats. The isolates showed the highest sensitivity to ciprofloxacin (25 mm inhibition zone), followed by chloramphenicol (8 mm) and tetracycline (7.33 mm), while resistance was observed against ampicillin.